Training on Financial Reporting and Projection of Business Feasibility for Residents of Bulu Cina Village, Hamparan Perak District, Deli Serdang Regency, North Sumatra - Muda, Iskandar; Erlina; Sembiring, Malinda Sari (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2023)
The purpose of this training is to carry out a Feasibility Study Analysis which includes an Internal Rate of Return (IRR) analysis, Payback Period and loan repayment analysis to the Buluh Cina Village government, Hamparan Perak Subdistrict, Deli Serdang and provide training on digital financial reports. Methods The training provided to the residents of Buluh Cina Village, Hamparan Perak Sub-district was carried out by making presentations to villagers who had the potential to run a business, this was carried out by the Service Team who served as resource persons. In this training, the Service Team also provides appropriate technology assistance in the form of: Excel Feasibility Study application in the form of entering elements of Income, Expenses, Bank Interest, Rate of Return, Payback Period and Decisions taken. The results achieved are the availability of a Feasibility Study Analysis application as well as a digital Financial Report application so that institutionally it meets the requirements as an adequate business organization. The advice given in this activity is to carry out monitoring and evaluation of the application of the Business Feasibility Study application and the application of Financial Statements.